(untitled) (CR. Conservación y Restauración, 2025)
In 2020, a program was generated for the prevention of theft and illicit trafficking of cultural heritage focused on the different groups that make up Mexican society. Within this framework, the Dirección de Atención Integral a Comunidades (DAIC) of the Coordinación Nacional de Conservación del Patrimonio Cultural (CNCPC), addressed the creation and design of the course Preventive Conservation. Prevention of theft of cultural property in religious buildings within communities. This consists of a series of tools, activities and contents organized and taught through the competency learning model, which also was arranged to allow the generation of quantitative and qualitative feedback that would help to prove the development of the competencies and skills by the attendants, and to keep the improvement of the course, as well. This article presents the process of structuring and designing the course along with the results and experiences of its delivery in 2021 and 2022 to communities in different states of the country.